Insights into the planetary dynamics of HD 206893 with ALMA. Issue 1 (31st August 2020) - Marino, S; Zurlo, A; Faramaz, V; Milli, J; Henning, Th; Kennedy, G M; Matrà, L; Pérez, S; Delorme, P; Cieza, L A; Hughes, A M
ABSTRACT: Radial substructure in the form of rings and gaps has been shown to be ubiquitous among protoplanetary discs. This could be the case in exo-Kuiper belts as well, and evidence for this is emerging. In this paper, we present ALMA observations of the debris/planetesimal disc surrounding HD 206893, a system that also hosts two massive companions at 2 and 11 au. Our observations reveal a disc extending from 30 to 180 au, split by a 27 au wide gap centred at 74 au, and no dust surrounding the reddened brown dwarf (BD) at 11 au. The gap width suggests the presence of a 0.9 M Jup planet at 74 au, which would be the third companion in this system. Using previous astrometry of the BD, combined with our derived disc orientation as a prior, we were able to better constrain its orbit finding it is likely eccentric (0.14^+0.05_-0.04 ). For the innermost companion, we used radial velocity, proper motion anomaly, and stability considerations to show its mass and semimajor axis are likely in the ranges 4–100 M Jup and 1.4–4.5 au. These three companions will interact on secular time-scales and perturb the orbits of planetesimals, stirring the disc and potentially truncating it to its current extent via secular resonances. Finally, the presence of a gap in this system adds to the growing evidence that gaps could be common in wide exo-Kuiper belts. Out of six wide debris discs observed with ALMA with enough resolution, four to five show radial substructure in the form of gaps.